EPID-02. Survival Experience in Pediatric Patients of Central Nervous System (CNS) Tumour in Canada. (3rd June 2022) - Yuan, Yan; Liu, JiaQi; Walker, Emily; Davis, Faith
Abstract: Established in 2016, the Brain Tumour Registry of Canada Surveillance Research Collaboration aims to address the lack of detailed information on CNS tumours in Canada. Using Canadian Cancer Registry (CCR) data with linked vital status, we present survival estimates for all primary CNS tumours (excluding Quebec) among pediatric patients (age 0-14). Pediatric patients diagnosed with primary CNS tumours during 2010-2017 were included. Vital status was obtained by Statistics Canada through linkage to the Canadian Vital Statistics Database and the income tax returns file, with a cut-off date of December 31, 2017. We used the Pohar-Perme method to estimate the net survival rate (NSR) through the period approach. International Classification of Diseases for Oncology (3rd edition) site/histology codes were grouped into 25 histological categories, irrespective of tumour behaviour, according to the schema developed by the Central Brain Tumor Registry of the United States. Of 1725 pediatric CNS tumours, the 1-, 2- and 5-year NSR are 0.89 (95%CI 0.87-0.90), 0.84 (95%CI 0.81-0.86) and 0.80 (95%CI 0.78-0.82), respectively. All non-malignant CNS tumours have a median survival over 8 years. The 5-year NSR range from 0.90 (95%CI 0.47-0.99) for unique astrocytoma variants, 0.95 for tumour of sellar region (95%CI 0.85-0.98) and germ cell tumours, cysts and heterotopias (95%CI 0.67-0.99), to 1.0 for choroid plexus tumours, tumours of cranial and spinal nerves, and meningioma. For malignant CNS tumours, NSR vary greatly depending on histology grouping. 5-year NSR from lowest to highest are glioblastoma (0.10, 95%CI 0.03-0.23), anaplastic astrocytoma (0.19, 95%CI 0.05-0.40), glioma not otherwise specified (0.54, 95%CI 0.46-0.62), embryonal tumours (0.72, 95%CI 0.65-0.79), diffuse astrocytoma (0.74, 95%CI 0.59-0.85), ependymal tumours (0.78, 95%CI 0.67-0.87), germ cell tumours, cysts and heterotopias (0.85, 95%CI 0.70-0.93) and pilocytic astrocytoma (1.0). We report the most comprehensive and up-to-date data on the pediatric primary CNS tumour survival experience in Canada.